The Juridical Implications of Changing the Function of Paddy Field Land to Residential Land - Larasati, Ayumi; Widayati, Widayati (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Indonesia is an agricultural country where agriculture is the main commodity as a producer of national food. Most Indonesian people still depend on the agricultural sector. Land is the main factor in the world of agriculture. As an agricultural country, Indonesia absorbs the largest number of workers in the agricultural sector compared to other economic sectors. The challenge in the agricultural sector is that there is less and less agricultural land because it has been eroded by human economic activities, especially changing its function to become a settlement. The conversion of paddy fields in Songgom District, Brebes Regency has experienced a significant increase. The purpose of this study aims to determine and analyze the process of converting land functions into residential land and the juridical implications of changing the function of paddy fields into residential land. The approach method in this study is a sociological juridical approach with research specifications used descriptive analysis. Where the author uses primary data sources obtained through interviews and secondary data obtained from the literature and then analyzed descriptively qualitatively. Based on the research, it was concluded that the process of transferring land use went through several stages starting from checking the spatial data zone whether it entered the yellow zone, which means it is normally converted, or the green zone, which means it cannot be converted because it is in an LSD area. If the yellow zone is included in the LSD zone area, it must be excreted from the LSD to the Regent, then make an application through the DPSDAPR office, after PERTEK exits, proceed with submitting an application for approval to the DPMPTSP/MPP office, then it will be returned to BPN to record changes in land use. Furthermore, it can only be sold/ready to be converted. The legal consequences of the conversion of agricultural land into a residential area for the perpetrators of land conversion that deviate from the rules, are regulated in Article 72 of Law Number 41 of 2009 concerning Sustainable Food Land: a. Individuals who change the function of sustainable food agricultural land as referred to in Article 44 paragraph (1) shall be subject to imprisonment for a maximum of 5 (five) years and a fine of up to IDR 1,000,000,000.00 (one billion rupiah), b. Individuals who do not carry out the obligation to restore the condition of sustainable food agricultural land to its original state as referred to in Article 50 paragraph (2) and Article 51 shall be punished with imprisonment for a maximum of 3 (three) years and a fine of up to IDR 3,000,000,000.00 (three billion rupiahs), c. In the event that the acts referred to in paragraphs (1) and (2) are committed by a government official, the penalty shall be added to 1/3 (one-third) of the penalty imposed.Keywords:Â Field; Housing; Juridical; Land.